PENGARUH IMPLEMENTASI RELATIONSHIP MARKETING TERHADAP CUSTOMER LOYALTY (STUDI KASUS PADA BANK MANDIRI CABANG BERINGHARJO DI DAERAH ISTIMEWA YOGYAKARTA) - Dhimas Nurcahyo; Ignatius Soni Kurniawan; Risal Rinofah (MANAJEMEN DEWANTARA, 2020)
The purpose of this study is to examine the effect of understanding customer expectations, building service partnerships, total quality management, and empowering employees towards customer loyalty. This research was conducted for customers who saved at Beringharjo Branch Bank Mandiri in the Special Region of Yogyakarta. The sampling technique in this study is cluster sampling. The study used questionnaires to collect primary data, and respondents were 80. We used regression analysis to determine the effect of understanding customer expectations, building service partnerships, total quality management, and empowering employees to customer loyalty. Comprehensively, the variable of understanding customer expectation, building service partnership, total quality management and empowering employees has a simultaneous and significant effect on customer loyalty. For the results of the coefficient of determination, it is explained that 61.3% of customer loyalty variants can be explained by the four independent variables.Kata kunci :Marketing relationship, understanding customer expectation, total quality management, empowering employees, customer loyalty.Â